2013
DOI: 10.1103/physrevb.87.035143
|View full text |Cite
|
Sign up to set email alerts
|

Spin-liquid versus spiral-order phases in the anisotropic triangular lattice

Abstract: We study the competition between magnetic and spin-liquid phases in the Hubbard model on the anisotropic triangular lattice, which is described by two hopping parameters t and t ′ in different spatial directions and is relevant for layered organic charge-transfer salts. By using a variational approach that includes spiral magnetic order, we provide solid evidence that a spin-liquid phase is stabilized in the strongly-correlated regime and close to the isotropic limit t ′ /t = 1. Otherwise, a magnetically order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 45 publications
(51 reference statements)
8
78
0
2
Order By: Relevance
“…E is symmetric with respect to t ′ /t = 0 owing to the electron-hole symmetry. 35 Similarly to the case on the frustrated square lattice, E(FS) and E(d−SC) (if the band renormalization is considered 115,116 ) are constant. For the ground state, we find from Fig.…”
Section: Anisotropic Triangular Latticementioning
confidence: 99%
“…E is symmetric with respect to t ′ /t = 0 owing to the electron-hole symmetry. 35 Similarly to the case on the frustrated square lattice, E(FS) and E(d−SC) (if the band renormalization is considered 115,116 ) are constant. For the ground state, we find from Fig.…”
Section: Anisotropic Triangular Latticementioning
confidence: 99%
“…It is well known that the perfect nesting of the square lattice means that is insulating for arbitrarily small U/t. For t = t, it is found, numerically, that the Mott transition occurs at around U/t = 10-15, depending on the method used [3,[15][16][17][18][19][20][21]79]. The metal-insulator transition line in Fig.…”
Section: Comparison With Organicsmentioning
confidence: 99%
“…This model contains three parameters: U the effective on-site Coulomb repulsion, t the nearest-neighbor hopping integral, and t the next-nearest-neighbor hopping integral along one diagonal only. The Hubbard model on the anisotropic triangular lattice has been studied via a number of approaches [15][16][17][18][19][20][21]. Some methods have suggested that a spin liquid is realized in the insulating phase.…”
Section: Introductionmentioning
confidence: 99%
“…If we average the two larger t's of Sb-1, assuming t = (t a + t b )/2 and t = t c , we find that the equivalent t − t model has t /t = 0.77. This model has been previously studied with variational Monte Carlo, 15 where for this value of t /t the critical U for the spinliquid transition is located at U/t ∼ 22, while for the FATL this value is strongly reduced to U/t a ∼ 11. On the other hand, the metal-insulator transition is only slightly affected, raising from U c /t ∼ 6 for the t − t model to U c /t a ∼ 6.75 for the FATL.…”
Section: B T − T Model Vs Fatlmentioning
confidence: 99%
“…In this way, we are able to treat spiral order and paramagnetic states at the same level of theory and therefore have a sensible comparison of their energies versus U . 15 …”
Section: B Effective Modelingmentioning
confidence: 99%